Emotional Intelligence as a psychological shield: a strategy to manage work stress in improving employee performance - Fatah, Rizki Azhari; Ardiansari, Anindya (Institute of Computer Science (IOCS), 2025)
Work stress is a psychological phenomenon that is increasingly prominent amid the complexity of the modern workplace. Excessive workloads, tight deadlines, and pressure from work systems and relationships can hinder productivity and reduce the quality of individual performance. However, not all individuals respond to stress in the same way. Emotional intelligence (EI), the ability to recognise, understand and manage one's own and others' emotions, has been shown to play an important role as a buffer against work pressure. This book chapter comprehensively examines how emotional intelligence can moderate the relationship between work stress and employee performance, by examining the theoretical foundations of organisational psychology, and mapping empirical evidence from relevant studies. Through a conceptual approach and critical reflection on current literature, this chapter also explores the strategic role of HRM in building a work environment that supports the development of employees' emotional intelligence, whether through training, coaching or organisational interventions. It emphasises how EI not only impacts on improving individual resilience to stress, but also becomes an important asset in creating healthy team collaboration, emotionally intelligent decision-making, and sustainable performance improvement. Therefore, the purpose of this chapter is to synthesize existing theoretical and empirical evidence to argue for the critical role of emotional intelligence as a psychological shield, and to provide actionable recommendations for integrating EI development into human resource management strategies to enhance employee performance and well-being. such, this chapter offers theoretical and practical contributions in bridging the need for organisations to increase productivity, while maintaining the psychological health of their workforce amidst evolving work demands.